Pengaruh Pengetahuan Kewirausahaan, Motivasi Berwirausaha dan Dukungan Sosial terhadap Intensi Berwirausaha Mahasiswa - Azizah, Wafik; Kadeni, Kadeni (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
Amid the difficulty of finding a job, entrepreneurial skills are becoming increasingly important. Final semester students are fased with an increasingly dynamic and competitive world of work. The hope is that by optimizing their potential, students can increase their entrepreneurial intention to create their jobs. This study aims to determine the influence of entrepreneurial knowledge, entrepreneurial motivation, and social support on entrepreneurial intention. This research is quantitative. The sample of this study were final semester students totaling 87 students with data collection techniques using a questionnaire. The analysis method used is multiple linear regression analysis. The results of this study indicate that entrepreneurial knowledge has a significant effect on entrepreneurial intention, entrepreneurial motivation has a significant effect on entrepreneurial intention, and social support has a significant effect on entrepreneurial intention. Based on the findings of this study, it is recommended that students increase entrepreneurial knowledge and entrepreneurial motivation because these two variables have a positive and significant effect on entrepreneurial intentions.